The Potential Protective Effect of Physalis peruviana L. against Carbon Tetrachloride-Induced Hepatotoxicity in Rats Is Mediated by Suppression of Oxidative Stress and Downregulation of MMP-9 Expression - Al-Olayan, Ebtisam M. (Hindawi Publishing Corporation, 2014)
The active constituent profile in Cape gooseberry (Physalis peruviana L.) juice was determined by GC-MS. Quercetin and kaempferol were active components in the juice. In this study we have evaluated its potential protective effect on hepatic injury and fibrosis induced by carbon tetrachloride (CCl(4)). Twenty-eight rats divided into 4 groups: Group I served as control group, and Group II received weekly i.p. injection of 2 mL CCl(4)/kg bwt for 12 weeks. Group III were supplemented with Physalis juice via the drinking water. The animals of Group IV received Physalis juice as Group III and also were intraperitoneally injected weekly with 2 mL CCl(4)/kg bwt for 12 weeks. Hepatoprotective effect was evaluated by improvement in liver enzymes serum levels, reduction in collagen areas, downregulation in expression of the fibrotic marker MMP-9, reduction in the peroxidative marker malonaldehyde and the inflammatory marker nitric oxide, and restoration of the activity of antioxidant enzymatic and nonenzymatic systems, namely, glutathione content, superoxide dismutase, catalase, glutathione-S-transferase, glutathione peroxidase, and glutathione reductase activities. The results show that the potential hepatoprotective effects of Physalis peruviana may be due to physalis acts by promotion of processes that restore hepatolobular architecture and through the inhibition of oxidative stress pathway.